Rekomendasi BUMDes Sebagai Solusi Masalah Pemasaran Hasil Produksi Pertanian Desa Hutabagasan - Yuni Mittra Simanullang; Tuti Atika (Yayasan Literasi Sains Indonesia, 2022)
The development of local community of Satahi Tani farming group in Hutabagasan Village aims to explore the problem faced and find solutions to overcome them. The method used in the devotion of the Satahi Tani peasant group is the Delbeq Method which is supported by FGD (Focus Group Discustion) tools aimed at focusing the topic of discussion. The results of the development of